2020
DOI: 10.3164/jcbn.19-77
|View full text |Cite
|
Sign up to set email alerts
|

Formation of neutrophil extracellular traps in mitochondrial DNA-deficient cells

Abstract: Neutrophil extracellular trap (NET) formation plays an important role in inflammatory diseases. Although it is known that NET formation occurs via NADPH oxidase (NOX) dependent and NOX independent pathways, the detailed mechanism remains unknown. Therefore, in this study, we aimed to elucidate the role of mito chondria in NOX dependent and NOX independent NET formation. We generated mitochondrial DNA deficient cells (ρ 0 cells) by treating HL 60 cells with dideoxycytidine and differentiated them to neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…Furthermore, we demonstrated that inhibition of mtROS reduces NET formation in response to Cdc42 inhibition in primary human neutrophils. This data is consistent with observations of Takishita et al showing that mitoTEMPO did not completely suppress NET formation in cells stimulated with the calcium ionophore A23187 and PMA ( 37 ). This group hypothesized that not only mtROS but also mitochondrial signaling is involved in NET formation in response to PMA and the calcium ionophore ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we demonstrated that inhibition of mtROS reduces NET formation in response to Cdc42 inhibition in primary human neutrophils. This data is consistent with observations of Takishita et al showing that mitoTEMPO did not completely suppress NET formation in cells stimulated with the calcium ionophore A23187 and PMA ( 37 ). This group hypothesized that not only mtROS but also mitochondrial signaling is involved in NET formation in response to PMA and the calcium ionophore ( 37 ).…”
Section: Discussionsupporting
confidence: 93%
“…To investigate the influence of mtROS on NET formation induced by PMA, ionomycin and Cdc42-inhibition, we used the mitochondria-restricted antioxidant mitoTEMPO to specifically inhibit mtROS. MitoTEMPO was described to act mitochondria specific to scavenge superoxide, thereby preventing mitochondrial damage ( 37 , 38 ). We could show that NET formation induced by PMA or ionomycin cannot be dampened by inhibiting mtROS formation ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“… 142 However, these data have been contradicted by other studies, which demonstrated that ATRA-dHL-60 cells can also react to CIs and DMSO-dHL-60 cells also to PMA. 143 , 144 …”
Section: The Hl-60 Cell Line As a Model For Human Neutrophilsmentioning
confidence: 99%
“…Importantly, Takishita et al found that the DNA expulsed by dHL-60 cells was genomic rather than mitochondrial, as removal of mitochondrial DNA had no effect on PMA-induced NET release. 143 …”
Section: The Hl-60 Cell Line As a Model For Human Neutrophilsmentioning
confidence: 99%
“…These NETs are more resistant to the action of DNases ( 64 ). In the formation of NETs by the independent way of NADPH oxidase, ROS come from the mitochondria and the blockade of MPO does not inhibit the extrusion of NETs, although it is partially dependent on MLKL ( 61 , 65 ). Processes such as vesiculation, DNA decondensation, release of nuclear DNA into the cytoplasm and expulsion of extracellular DNA can be observed in this pathway ( 66 ).…”
Section: Organisms That Produce Extracellular Trapsmentioning
confidence: 99%